GAMBARAN POLA PERESEPAN ANTIBIOTIK PADA PASIEN ISPA RAWAT JALAN DI POLIKLINIK ANAK RUMAH SAKIT X DI GIANYAR - Gede Trima Yasa (Institut Teknologi dan Kesehatan Bintang Persada, 2022)
Acute Respiratory Infection (ARI) is a disease that is still a health problem in developing countries, including Indonesia. Administration of antibiotics is one of the treatments for ARI.The supporting factor for the success of drug therapy, especially antibiotics is the accuracy in prescribing antibiotics. This study aims to determine the pattern of antibiotic prescribing in outpatient ARI patients at the children's polyclinic at RSU Premagana. The method used in this research is cross-sectional with purposive sampling technique. Data were taken using prescription sheets and medical records of ARI patients for the period October-December 2021. The results of this study that from 164 samples, the characteristics of ARI patients were dominated by children aged 0-5 years (83.5%) with the highest gender in men (61%). The diagnosis of ARI is classified by the distribution of nasopharyngitis (33,5%), non-specific ARI (28,0%), acute pharyngitis (25,6%), tonsillitis (9,1%) and tronchiolitis (3,7%). The most commonly prescribed class of antibiotics is the third generation cephalosporin of the cefixime type (56.7%) and the first generation cephalosporin group, cefadroxil (39.0%) with the type of antibiotics single therapy (100%). Based on the diagnosis, cefixime most given to ARI not specific and pharyngitis, while cefadroxil is mostly given to nasopharyngitis and tonsillitis Keywords: Dagusibu, Knowledge Level, Drugs